Somatic copy number variant mutations in alpha-synuclein and genome-wide in brains of synucleinopathy cases. Issue 6 (27th May 2022) - Perez-Rodriguez, Diego; Kayla, Maria; Leija-Salazar, Melissa; Lashley, Tammaryn; Warner, Thomas; Gentleman, Steve; Schapira, Anthony; Holton, Janice; Jaunmuktane, Zane; Proukakis, Christos
Abstract : Synucleinopathies are mostly sporadic neurodegenerative disorders, and include Parkinson's disease (PD), and multiple system atrophy (MSA). Inherited copy number variants (CNVs) of SNCA (α-synuclein) are rare causes of familial disease. There is increasing evidence for somatic mutations in the human brain, and we have hypothesized a role for these in synucleinopathies. We further investigated somatic CNVs in brains from synucleinopathy cases, using Fluorescent in-situ Hybri- disation for SNCA gains, and single-cell whole genome sequencing for the first time in a synucleinopathy. In the cingulate cortex, mosaicism for SNCA gains was higher in MSA and PD than controls in neurons (> 2% in both diseases), and for MSA also in non-neurons. In MSA substantia nigra (SN), we noted SNCA gains in > 3% of cells. Cells with CNVs were more likely to have α-synuclein inclusions, in a pattern corresponding to cell categories mostly relevant to the disease: dopaminergic neurons in Lewy-body cases, and other cells in striatonigral degeneration-dominant MSA (MSA-SND). Higher SNCA CNV mosaicism in typical MSA-SND SN non-dopaminergic cells may correlate with younger onset, and in PD cingulate neurons with younger death. Whole genome sequencing of 169 single cells from two MSA cases showed somatic CNVs in ~ 30%. Neurons had gains and losses, and other cells almost exclusively gains. We propose that somatic SNCA CNVs contribute to the aetiology and pathogenesis of synucleinopathies, and that genome-wide somatic CNVs merit further study c.proukakis@ucl.ac.uk